Perancangan Perangkat Lunak Pembelajaran Mikroprosesor Dengan Menggunakan Metode Computer Assisted Instruction - Berto Nadeak; Sony Bahagia Sinaga (JUKI : Jurnal Komputer dan Informatika, 2020)
The microprocessor that became the machine for the IBM PC / XT microcomputers and their compatible. This processor is often referred to as simply "8088" or "8086". Although the hardware of the 8088 is slightly different from the 8086, they can be viewed as the same from a programming perspective. The Intel 8088/8086 is a 16 bit processor, meaning that the data path and registers are 16 bits in size. The addressing mode is divided into several types, among others, register addressing, immediate addressing, direct addressing and indirect addressing. In addition, in learning Assembly language, we must memorize all registers and understand their use. Computer Aided Instruction (CAI) is a variety of information in the way of learning. Computers as a medium will help students find new things that are more interesting than conventional teacher-centered ways. Although it is known that the ways of learning and teaching, as well as the acquisition of learning information for each individual are different.